Microencapsulation technology for delivery of enzymes in ruminant feed - Almassri, Nada; Trujillo, Francisco J.; Terefe, Netsanet Shiferaw (Frontiers in Veterinary Science, 2024)
The ruminant digestive system is uniquely designed to make efficient use of high-fibre feed, including forages. Between 40 to 100% of the ruminant diet consists of forages which are high in fibre and up to 70% of this may remain undigested in the ruminant gut, with substantial impact on feed utilisation rate and productivity and the economic and environmental sustainability of livestock production systems. In ruminants, feed costs can make up to 70% of the overall cost of producing an animal product. Increasing feed utilization efficiency i.e., more production with less feed lowers feeding costs and improves livestock economic viability.Strategies for improving the nutrient utilization in animal feed has been investigated over the years. Incorporation of fibre digesting enzymes in the feed to facilitate the digestion of the residual fibre in hind gut is one of the proposed strategies. However, delivering such enzymes to the hind gut in active state is challenging due to the unfavourable biochemical environment (pH, microbial proteases) of ruminant's gastrointestinal tract. This review discusses the potential application of microencapsulation for protected and targeted delivery of enzymes into the hind gut of ruminants.